EVALUASI EFEKTIVITAS PELAKSANAAN PENGADAAN BARANG DAN JASA PADA PT PLN (Persero) WILAYAH SULSEL, MAKASAR - , ASTUTY HASTI, Prof. Dr. Gudono, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research was motivated because of the acts of corruption, collusion and nepotism in the procurement of goods and services. For that the issuance of Presidential Decree Number 54 of 2010 which regulates the procedures and procedures for the procurement of goods and services by implementing an electronic based system that LPSE systems based e-procurement. Based on the existing strengths in e-procurement, the researchers conducted a compliance audit is to evaluate the effectiveness of the procedures established by the government in PT PLN Makassar region as one of the BUMN that have used e-procurement in the procurement of goods and services with funds from the state budget. The purpose of this study is to investigate, identify, analyze, and provide recommendations on the implementation of procurement procedures for goods and services through e-procurement is already working effectively based on the guidelines on procedures for implementing the procedures of procurement of goods and services that have been issued by the Government of the Presidential Decree 54 in 2010. The results of this study demonstrate the application of e-procurement in PT PLN (Persero) Makassar area has not been fully effective. Not because of the distortion factor but on the procurement of goods and services considered to have not fully able to operate because of a lack of guidance in terms of the direct practice of using e-procurement system, but only focuses on the theory with a discussion of a fairly dense and very short time. But judged in terms of budget, the use of e-procurement is considered very efisien.karena realization of achievement in the year 2011 reached 99.97%, although the application of e-procurement has begun. Obstacles encountered in implementing the procurement of goods and services using eprocurement is to operate the e-procurement itself. So that the application of e-procurement rated slow